2022
DOI: 10.1002/adfm.202200893
|View full text |Cite
|
Sign up to set email alerts
|

Nickel–Platinum Alloy Nanocrystallites with High‐Index Facets as Highly Effective Core Catalyst for Lithium–Sulfur Batteries

Abstract: Elemental sulfur possesses an ultra-high theoretical specific capacity, while the practical application of sulfur in lithium-sulfur (Li-S) batteries is seriously hindered by the sluggish redox kinetics and serious shuttle effect. Enhancing the catalytic activity of the sulfur host by a rational structural design is the key to address these issues. Herein, for the first time, concave-nanocubic (CNC) nickel-platinum (Ni-Pt) alloys bounded by high-index facets (HIFs) are introduced as the core catalyst of sulfur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…Introducing foreign elements to form Pt-based alloy materials could enhance electron conductivity, optimize the electron structure, and provide sufficient synergistic function of the material. In addition, a three-dimensional (3D) open structure with multi-channels could not only expose enough active sites and improve utilization of Pt but also limit the reactants in nanoscale spaces to increase the collision frequency during the catalytic reaction process. The high-index facets are considered to be an open structure represented by a set of Miller indices { hkl }, which have rich low coordination atoms, providing more active sites for the catalytic process. However, the reported performance of bifunctional catalysts for HER and EOR is still unsatisfactory. Therefore, it is challenging and significant to develop Pt-based alloy electrocatalysts with 3D open structures and high-index facets for superior bifunctional performance (HER and EOR).…”
Section: Introductionmentioning
confidence: 99%
“…Introducing foreign elements to form Pt-based alloy materials could enhance electron conductivity, optimize the electron structure, and provide sufficient synergistic function of the material. In addition, a three-dimensional (3D) open structure with multi-channels could not only expose enough active sites and improve utilization of Pt but also limit the reactants in nanoscale spaces to increase the collision frequency during the catalytic reaction process. The high-index facets are considered to be an open structure represented by a set of Miller indices { hkl }, which have rich low coordination atoms, providing more active sites for the catalytic process. However, the reported performance of bifunctional catalysts for HER and EOR is still unsatisfactory. Therefore, it is challenging and significant to develop Pt-based alloy electrocatalysts with 3D open structures and high-index facets for superior bifunctional performance (HER and EOR).…”
Section: Introductionmentioning
confidence: 99%
“…A cathode substrate configured with boron-carbide (B 4 C) nanowires in situ grown on carbon nanofibers was synthesized and reported by Luo et al, which effectively enhanced the cycling stability of the LSBs . In addition to the introduction of a single metal compound, the use of alloy materials with upgraded catalytic activity through the synergism of different components proves another valid means as well. Apart from the low cost of iron (Fe) and nickel (Ni), the performance of LSBs can be remarkably enhanced using iron and nickel alloys. As one kind of heterostructure, the metal alloy has many unique merits, including the advantages inherited from each component .…”
Section: Introductionmentioning
confidence: 99%
“…has been rarely explored in the LSBs. According to reports, the filling of the noble metal d-band originated from the difference in electronegativity between noble metals and transition metals, accompanied by a downshift in the central energy of the d-band, resulting in an optimized electronic structure and corresponding catalytic activity significantly higher than that of single metal-based catalysts. Wang et al reported that the well-designed nickel–platinum alloy as a catalyst dispersedly loaded on graphene provides modest chemical anchoring for LiPSs, decreases the energy barriers of catalytic conversion, and expedites the kinetics of LiPS intermediates . Through investigation, we found that iridium (Ir) is a 5d transition metal with unique properties in electrochemical catalysis compared to some other noble metals (such as Au and Pt) because of its good compatibility with electrolytes, which is beneficial for reducing charge polarization. , Thus, it is a promising approach to tune the electronic structure of Ir sites by coupling the thiophilic Cu, which was highly conductive, naturally abundant, and of low-cost. , …”
Section: Introductionmentioning
confidence: 99%
“…16−18 Wang et al reported that the well-designed nickel−platinum alloy as a catalyst dispersedly loaded on graphene provides modest chemical anchoring for LiPSs, decreases the energy barriers of catalytic conversion, and expedites the kinetics of LiPS intermediates. 19 Through investigation, we found that iridium (Ir) is a 5d transition metal with unique properties in electrochemical catalysis compared to some other noble metals (such as Au and Pt) because of its good compatibility with electrolytes, which is beneficial for reducing charge polarization. 7,20 Thus, it is a promising approach to tune the electronic structure of Ir sites by coupling the thiophilic Cu, which was highly conductive, naturally abundant, and of low-cost.…”
Section: Introductionmentioning
confidence: 99%